IL-17A is essential to the development of elastase-induced pulmonary inflammation and emphysema in mice - Kurimoto, Etsuko (BioMed Central, 2013)
BACKGROUND: Pulmonary emphysema is characterized by alveolar destruction and persistent inflammation of the airways. Although IL-17A contributes to many chronic inflammatory diseases, it’s role in the inflammatory response of elastase-induced emphysema remains unclear. METHODS: In a model of elastase-induced pulmonary emphysema we examined the response of IL-17A-deficient mice, monitoring airway inflammation, static compliance, lung histology and levels of neutrophil-related chemokine and pro-inflammatory cytokines in bronchoalveolar lavage (BAL) fluid. RESULTS: Wild-type mice developed emphysematous changes in the lung tissue on day 21 after elastase treatment, whereas emphysematous changes were decreased in IL-17A-deficient mice compared to wild-type mice. Neutrophilia in BAL fluid, seen in elastase-treated wild-type mice, was reduced in elastase-treated IL-17A-deficient mice on day 4, associated with decreased levels of KC, MIP-2 and IL-1 beta. Elastase-treated wild-type mice showed increased IL-17A levels as well as increased numbers of IL-17A+ CD4 T cells in the lung in the initial period following elastase treatment. CONCLUSIONS: These data identify the important contribution of IL-17A in the development of elastase-induced pulmonary inflammation and emphysema. Targeting IL-17A in emphysema may be a potential therapeutic strategy for delaying disease progression.